Amphibians of North Africa - Escoriza, Daniel; Hassine, Jihene Ben (Academic Press, an imprint of Elsevier, 2019)
Amphibians of North Africa is a comprehensive compilation of available data on the amphibians and reptiles found in various ecosystems across North West Africa and parts of the Mediterranean region. It is essential to identifying and understanding the ecological role of regional herpetofauna and its conservational importance. It examines the biological origins and diversity of amphibians in North Africa, along with their diverse ecosystems, including deserts, grasslands and subtropical forests. The book features detailed descriptions of the adult and larvae stages of species, such as the North African fire salamander, the common painted frog, Brongersma's toad and the Mediterranean tree frog. This book is a vital resource for herpetology and ecology students and researchers, helping them identify, understand and conserve these amphibians and reptiles in their various habitats across the North African and Mediterranean regions.